Histamine reduces boron neutron capture therapy-induced mucositis in an oral precancer model - Monti Hughes, Andrea (2015)
Fil: Monti Hughes, Andrea. Comisión Nacional de Energía Atómica. Departamento de Radiobiología; Argentina